Promotion of socially responsible business in transport companies in Serbia - Žarevac Bošković, Milica; Lakićević, Marija; Pantović, Danijela (Anali Ekonomskog fakulteta u Subotici, 2021)
The topic of this paper represents a relatively new and still evolving term of socially responsible business, with a focus on application of this concept to transport companies. The goal of this paper is to formulate, in accordance with results gained from the study, concrete potential guidelines for more socially responsible business of transport companies in the Republic of Serbia. Considering multiple positive effects of socially responsible business, confirmed by numerous study activities and practical examples, as well as the fact that influences on one of the key external dimensions of socially responsible business – the environment – are most directly connected with transport business, and, finally, observing traffic as connective tissue of the entire economic system that gives purpose to all areas of material production, this paper analyses, in addition to the nature of the link between economic and social performance, the degree of application of socially responsible business in transport companies in the Republic of Serbia as well.